2007
DOI: 10.1523/jneurosci.4340-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C Is Required for Changes in Postsynaptic Structure and Function Associated with NMDA Receptor-Dependent Long-Term Depression

Abstract: AKAP79/150 is targeted to spines through binding F-actin and the phospholipid phosphatidylinositol-(4,5)-bisphosphate (PIP 2 ). Previous electrophysiological studies have demonstrated that inhibition of phospholipase C (PLC)-catalyzed hydrolysis of PIP 2 inhibits NMDAR-dependent LTD; however, the signaling mechanisms that link PLC activation to alterations in dendritic spine structure and AMPAR function in LTD are unknown. We show here that NMDAR stimulation of PLC in cultured hippocampal neurons is necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
102
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 86 publications
(187 reference statements)
10
102
1
Order By: Relevance
“…11G-I ). It has been shown that neurons exposed to a chemical LTD protocol change spine morphology (Halpain et al, 1998;Horne and Dell'Acqua, 2007). Indeed, bath application of 50 M NMDA significantly decreased the number of spines, without affecting protrusion density (Fig.…”
Section: Eb3 Overexpresssion Protects Spines Against Ltd-induced Spinmentioning
confidence: 87%
“…11G-I ). It has been shown that neurons exposed to a chemical LTD protocol change spine morphology (Halpain et al, 1998;Horne and Dell'Acqua, 2007). Indeed, bath application of 50 M NMDA significantly decreased the number of spines, without affecting protrusion density (Fig.…”
Section: Eb3 Overexpresssion Protects Spines Against Ltd-induced Spinmentioning
confidence: 87%
“…The observation that NMDA application activates calcineurin and that the stimulatory effect of NMDA application on AMPA receptor endocytosis is blocked by calcineurin antagonists (47) is consistent with a model in which postsynaptic SJ1 is involved in mediating some of the effects of NMDA receptor activation. Interestingly, a recent study showed that decrease of PI(4,5)P 2 is required to trigger internalization of AMPA receptors in response to NMDA activation, and that inhibition of PLC, another manipulation that enhances PI(4,5)P 2 levels, impairs NMDA-induced AMPA receptor internalization and long-term depression (48).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that PSD-95 decreases dendrite branching by disrupting microtubule organization (Charych et al, 2006;Sweet et al, 2011a,b). Moreover, PSD-95 is in a complex with F-actin, and PSD-95 overexpression enhances dendritic spine formation and stabilization (Okabe et al, 1999;El-Husseini et al, 2000;Horne and Dell'Acqua, 2007). Cypin increases dendrite branching by promoting microtubule polymerization and negatively regulating PSD-95 clustering (Firestein et al, 1999;Akum et al, 2004;Charych et al, 2006).…”
Section: Introductionmentioning
confidence: 99%